Functional Redundancy and Specialization of the Conserved Cold Shock Proteins in Bacillus subtilis - Patrick Faßhauer; Tobias Busche; Jörn Kalinowski; Ulrike Mäder; Anja Poehlein; Rolf Daniel; Jörg Stülke (Microorganisms, 2021)
Many bacteria encode so-called cold shock proteins. These proteins are characterized by a conserved protein domain. Often, the bacteria have multiple cold shock proteins that are expressed either constitutively or at low temperatures. In the Gram-positive model bacterium Bacillussubtilis, two of three cold shock proteins, CspB and CspD, belong to the most abundant proteins suggesting a very important function. To get insights into the role of these highly abundant proteins, we analyzed the phenotypes of single and double mutants, tested the expression of the csp genes and the impact of CspB and CspD on global gene expression in B. subtilis. We demonstrate that the simultaneous loss of both CspB and CspD results in a severe growth defect, in the loss of genetic competence, and the appearance of suppressor mutations. Overexpression of the third cold shock protein CspC could compensate for the loss of CspB and CspD. The transcriptome analysis revealed that the lack of CspB and CspD affects the expression of about 20% of all genes. In several cases, the lack of the cold shock proteins results in an increased read-through at transcription terminators suggesting that CspB and CspD might be involved in the control of transcription termination.